A review : assessment of stabilization dust using liquid enzymes - Firoozi, Ali Akbar; Firoozi, Ali Asghar; Naji, Maryam; Ernest, Chanana (Penerbit Universiti Kebangsaan Malaysia, 2021)
Roads play a significant part of economic development. Due to financial constraints, in many developing countries like Botswana, there are large networks of unpaved roads. The major detriment effect of unpaved or gravel roads is dust emissions. Dust affects the climate change which in turn increases the generation of dust. This has a huge impact on human health which has risen to great concern. The best solution to mitigate dust emission from gravel roads is to seal the gravel roads but this cannot be easily achieved due to financial constraints. Traditionally, road managers have controlled dust by applying calcium chloride or magnesium chloride to the road surface. However, these salts easily leach out of the soil during precipitation events and may not be an option in environmentally sensitive areas. Bio-enzymes have emerged as environmentally friendly soil stabilizers. They are cheap and can easily be available. In this review paper the use of bio-enzymes as stabilizers and a solution to reducing dust will be reviewed, health effects of dust in this exercise to try and see if they can mitigate dust on earth roads that have been constructed using material at site or calcrete. The findings could spread the awareness of effects of dust in Botswana so that the public and private sector can help in supplying the enzymes to reduce health issues affecting the society in Botswana. It will also help decision-makers to make a wise choice of which bio-enzyme to be used effectively.